Business Feasibility Study of Nindi Tempe Factory Based on Production and Financial Aspects - Aisyah Fahrenzo; Andi Afrizal; Hendry Kurniawan (PT. Hidayat Muda Intelektual, 2025)
The purpose of this study is to analyze the progress of the tempeh factory which is analyzed in terms of technical aspects of production and financial aspects. Analysis of technical and production aspects is a critical stage in assessing a company's readiness to run a business. In line with the technical aspects, financial analysis plays a fundamental role in determining the feasibility of a business so that business actors can make strategic decisions based on accurate calculations, to minimize the risk of loss and maximize potential profits. This study uses a qualitative method through a descriptive approach. carried out in order to see the prospects and feasibility of the Nindi tempeh factory business in Pasar Baru Village, Ujung Batu District. This study was conducted at the Nindi tempeh factory business in Pasar Baru Village, precisely in Ujung Batu District. With a business feasibility study analysis based on technical and production aspects and financial aspects.